Using Hierarchical Cluster and Factor Analysis to Classify and Built a phylogenetic Tree Species of ND1 Mitochondria - Ibrahim, Ali A; Al Rikabi, Zainib H A; Ahmed, Najwa Sh (Al-Nahrain Journal of Science, 2018)
The research amied to classify and characterize 11 different organisms according to amino acid sequencing of ND1 mitochondria gene by using the two analysis methods of factor analysis and cluster analysis, in order to achieve this goal, we collected amino acid sequencing from Database of national center biotechnology information (NCBI) for eleven organisms (human, chimpanzee, monkeys, cow, horse, mouse, rat, fish, frog, chicken and rabbit) and this was one of the most important of the results which was as follows: A: By using factor analysis the organisms was classified into six groups. B: By using cluster analysis the organisms was classified into four groups. Each group did included similar number of organism, they were identical with each other. This was a result of a similar chain peptide multiple for ND1. Results of the two methods (cluster and factor analysis) were cluster organisms (human and chimpanzee and monkey) in one group and was the lowest value between humans and chimpanzees, with distance equal to 0.09, the great affinity between the human and chimpanzee and monkey and clustering of chicken as a single group and reached the highest value between human and chicken with distance equal to 0.642012 and to move away genetic traits to humans from chicken. The conclusion factor analysis method was able to give more precise details of the method from cluster analysis through the. identification and clustering of new groups with genetic dimension for the other group.